2001
DOI: 10.1103/physrevlett.86.4664
|View full text |Cite
|
Sign up to set email alerts
|

Unique Spin Dynamics and Unconventional Superconductivity in the Layered Heavy Fermion CompoundCeIrIn5: NQR Evidence

Abstract: We report measurements of the 115 In nuclear spin-lattice relaxation rate (1/T1) between T =0.09 K and 100 K in the new heavy fermion (HF) compound CeIrIn5. At 0.4 K ≤ T ≤ 100 K, 1/T1 is strongly T -dependent, which indicates that CeIrIn5 is much more itinerant than known Ce-based HFs. We find that 1/T1T , subtracting that for LaIrIn5, follows a ( 1 T +θ ) 3 4 variation with θ=8 K. We argue that this novel feature points to anisotropic, due to a layered crystal structure, spin fluctuations near a magnetic orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
127
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 27 publications
15
127
0
Order By: Relevance
“…Antiferromagnet CeRhIn 5 becomes superconducting at relatively lower critical pressure P c ∼ 1.6 GPa and yet exhibits a higher T c ∼ 2 K [1]. Measurements of nuclear-quadrupole-resonance (NQR) [4,5,6,7], thermal transport and heat capacity [8] on CeMIn 5 found that the superconductivity is unconventional, with line-nodes in the superconducting gap function. NQR [4,5,7,9] and inelastic neutron diffraction [10] measurements also found strong antiferromagnetic spin fluctuations in the normal state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antiferromagnet CeRhIn 5 becomes superconducting at relatively lower critical pressure P c ∼ 1.6 GPa and yet exhibits a higher T c ∼ 2 K [1]. Measurements of nuclear-quadrupole-resonance (NQR) [4,5,6,7], thermal transport and heat capacity [8] on CeMIn 5 found that the superconductivity is unconventional, with line-nodes in the superconducting gap function. NQR [4,5,7,9] and inelastic neutron diffraction [10] measurements also found strong antiferromagnetic spin fluctuations in the normal state.…”
mentioning
confidence: 99%
“…Measurements of nuclear-quadrupole-resonance (NQR) [4,5,6,7], thermal transport and heat capacity [8] on CeMIn 5 found that the superconductivity is unconventional, with line-nodes in the superconducting gap function. NQR [4,5,7,9] and inelastic neutron diffraction [10] measurements also found strong antiferromagnetic spin fluctuations in the normal state. In addition, in CeIrIn 5 , the antiferromagnetic spin fluctuations are found to be anisotropic [4], namely, a magnetic correlation length ξ plane within the tetragonal plane grows up more dominantly than ξ c along the c-axis associated with their two-dimensional crystal structure.…”
mentioning
confidence: 99%
“…Monthoux et al [134], however, emphasize that this kind of magnetically mediated superconductivity is sensitive to small changes in the band structure, possibly yielding an explanation why CeRhIn 5 with a c/a ratio intermediate between CeIrIn 5 and CeCoIn 5 only exhibits superconductivity below T c = 110 mK. For the entire series of CeT In 5 compounds, both the specific heat [135] and the spin-lattice relaxation rate divided by temperature 1/T 1 T , measured by means of NQR [136][137][138], provide compelling evidence for the existence of line nodes in the superconducting energy gap and therefore unconventional superconductivity.…”
Section: Cein 3 and Cemin (M = Co Ir Rh)mentioning
confidence: 99%
“…[5][6][7] CeRhIn 5 , an antiferromagnet with Néel temperature T N = 3.8 K at ambient pressure, becomes superconducting near 2 K, with suppression of the antiferromagnetism, at applied pressure of P * ∼ 2 GPa. 8 Systematic nuclear magnetic resonance (NMR) investigations of the Ce115 systems have established that these superconductors have d-wave superconducting gaps, [9][10][11][12] and that antiferromagnetic (AFM) spin interactions play an active role in the superconducting pairing. [13][14][15][16] In the Pu115 systems, NMR measurements show d-wave-like superconducting gap behavior, 17,18 with T c 's an order of magnitude higher than those for the Ce115.…”
Section: Introductionmentioning
confidence: 99%